2018
DOI: 10.5897/err2018.3469
|View full text |Cite
|
Sign up to set email alerts
|

Mental health and inclusion seen from the childrens and teachers perspectives: A case study in Spain

Abstract: Inclusive school requires the coexistence of what is perceived as normal and what is seen as pathologically different.Considering the growing pathologization of childhood, attempt is made to know the view of the students that do not have any diagnosed mental disorder on the ones that do have and the teachers' view on the inclusion of these children. A case study was conducted in a Spanish public primary school that has an inclusive pedagogical project. Semi-structured interviews and questionnaires were used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Nevertheless, in ten studies the attitudes are mixed: five of them are in-service teachers' studies [26,33,35,44,50], three are pre-service teachers' research [24,37,57], another one is a mixed study with in-service and preservice teachers [61], and the last one that found mixed attitudes was conducted just with special education teachers [32]. In three other cases, teachers' attitudes toward inclusion tended to be even negative [22,30,52].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in ten studies the attitudes are mixed: five of them are in-service teachers' studies [26,33,35,44,50], three are pre-service teachers' research [24,37,57], another one is a mixed study with in-service and preservice teachers [61], and the last one that found mixed attitudes was conducted just with special education teachers [32]. In three other cases, teachers' attitudes toward inclusion tended to be even negative [22,30,52].…”
Section: Discussionmentioning
confidence: 99%